RANCANG BANGUN PROTOTIPE PEMBANGKIT LISTRIK TENAGA PIKOHIDRO BERBASIS KONTROL ARDUINO UNO - Muchamad Sobri Sungkar; Givy Devira Ramady; Andrew Ghea Mahardika; Hetty Fadriani; Asep Hilmi Mutaqin (Politeknik Harapan Bersama Tegal, 2021)
Abstract Electrical energy is a very vital energy and plays an important role in the development of human technology. Almost all devices in the world use electrical energy as a source of energy. Indonesia is a country that has a large enough water energy potential of around 75,650 MW, 6% of which has been developed in various forms of research, especially in locations outside the islands of Java and Bali in the form of utilizing river water as a Pico Hydro Power Plant (PLTPH) to meet the needs of electrical energy in remote and remote areas. The design of this PLTPH prototype aims to analyze the output voltage generated by the generator which is influenced by the flow of water in the system which has been equipped with sensors monitoring current, voltage, rpm and water discharge which then the results can be seen in real time through the LCD screen. In this test, it is also known that the water discharge affects the output voltage produced by the generator, the greater the water discharge, the greater the output voltage.